Fine needle aspiration in intraocular metastasis from pleuropulmonary blastoma. A case report and a review of the literature. Issue 2 (8th October 2016) - Costa, Jennifer; Klijanienko, Jerzy; Desjardins, Laurence; Cassoux, Nathalie; Machet, Marie Christine; Pacquement, Helene
Abstract : Pleuropulmonary blastoma (PPB) is a rare primitive intrathoracic malignant neoplasm that occurs almost exclusively in children and adolescents. PPB is classified into three types according to the presence of cystic and solid areas. We report a case of PPB with an intraocular metastasis diagnosed by fine needle aspiration (FNA): 3‐year‐old female was treated for type II PPB by neoadjuvant chemotherapy and surgery. Four years later, she presented with an intraocular lesion. To differentiate between metastasis or other malignancy, a transcleral FNA was performed and showed two cellular populations represented by roundish malignant cells and spindle‐shaped cells. The patient was treated with chemotherapy and diode laser ablation. A year later, the patient had enucleation and rare residual cells were found on the histological specimen. Patient remains disease‐free 66 months after the last surgical treatment. Diagn. Cytopathol. 2017;45:156–160. © 2016 Wiley Periodicals, Inc.